Uji Performa Engine Fuel Injection Berbahan Bakar Gasoline-Butanol dan Gasoline-Ethanol - Firman Lukman Sanjaya; Faqih Fatkhurrozak; Syarifudin Syarifudin; M. Khumaidi Usman; Andre Budhi Hendrawan (P3M Politeknik Negeri Cilacap, 2025)
The energy crisis is largely attributed to the extensive use of fossil fuels. Butanol and ethanol can be used as an alternative energy source because their characteristics are superior to those of gasoline, such as RON and oxygen content. This study aims to determine the effect of gasoline-butanol and gasoline-ethanol mixtures on engine performance so that they can be an option to replace fossil fuels. The percentage of alcohol (butanol and ethanol) in gasoline is 5%, 10%, and 15% with variations in engine speed of 1000, 2000, and 3000 rpm. This study uses a dynamometer as a tool to measure engine performance. Test results show that E15 can increase engine torque and power by up to 26%, while B15 increases by 19%. In addition, ethanol can reduce BSFC better than butanol. The BSFC value decreased by 17% in E15, while B15 decreased by 15% compared to pure gasoline. This is because ethanol's RON and oxygen content are higher, so torque and power increase while BSFC decreases. These results prove that gasoline-ethanol is better at improving engine performance than gasoline-butanol.